Catalytic Conversion of Lignin: Studies on Oxidation of Lignin Model Phenolic Monomer over CoMCM-41 and CoMCM-48 Catalysts - Sadual, R.; Sahoo, S.; Badamali, S.K. (Asian Journal of Chemistry, 2017)
The present study focussed on investigation of the potentiality of cobalt containing mesoporous material (M41S) as a robust heterogeneous catalyst for the oxidation of lignin model phenolic compound. Cobalt containing MCM-41 and MCM-48 were prepared under hydrothermal condition and characterized by various spectroscopic and analytical techniques. Formation of well ordered hexagonal and cubic mesopore structures of MCMs, containing cobalt in the silicate framework was inferred from XRD, TG-DTA and N2 adsorption-desorption studies. DR UV-visible spectral analysis revealed existence of Co(II) and Co(III) in the tetrahedral framework. The oxidative ability of CoMCMs were studied for the lignin model phenolic monomer, 1-(4-hydroxy-3-methoxyphenoxy)-ethanol, under mild conditions using environmentally benign H2O2 as the oxidant. The catalytic results showed that under optimum reaction conditions, apocynol undergoes selective oxidation yielding 2-methoxybenzoquinone and acetovanillone. CoMCM-41 was found to be more selective towards acetovanillone, on the contrary, CoMCM-48 was better catalyst for 2-methoxybenzoquinone yield.